2001
DOI: 10.1016/s0014-5793(01)02420-6
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene glycol induces apoptosis in HT‐29 cells: potential mechanism for chemoprevention of colon cancer

Abstract: Recent experimental evidence suggests that polyethylene glycol (PEG) is a highly effective chemopreventive agent against colon cancer; however, the mechanism(s) remain largely unexplored. To further elucidate this issue, we evaluated the effect of PEG on two human colon cancer cell lines. PEG treatment resulted in a dose-and time-dependent reduction in cell number without alteration in markers of cell proliferation. However, there was a dramatic and specific, concentrationdependent induction of apoptosis, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 27 publications
(37 reference statements)
1
20
0
Order By: Relevance
“…Our results from the cell culture, in keeping with the study from Corpet's laboratory (26), indicate that PEG has a marked cytoprotective effect. Furthermore, antiproliferative effect of PEG complements its proapoptotic effect that we have previously reported in cell culture, azoxymethane-treated rat, and the MIN mouse (17,41).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Our results from the cell culture, in keeping with the study from Corpet's laboratory (26), indicate that PEG has a marked cytoprotective effect. Furthermore, antiproliferative effect of PEG complements its proapoptotic effect that we have previously reported in cell culture, azoxymethane-treated rat, and the MIN mouse (17,41).…”
Section: Discussionsupporting
confidence: 71%
“…Epidermal growth factor receptor is known to induce SNAIL (49). Another point that needs to be emphasized is that whereas our article focuses on proliferation, we have previously shown that PEG also induces apoptosis in animal models and cell culture (17,41). Clearly, both SNAIL and h-catenin have important effects on apoptosis.…”
Section: Discussionmentioning
confidence: 87%
“…In the studies on AOM-induced ACF suppression, the optimal formulation of PEG has been shown to be PEG-8000, though understanding its molecular targets may help redefine the specificity and effectiveness of other formulations. Previous reports on PEG's potential mechanism of action have suggested number of possibilities i.e., suppression of proliferation, induction of apoptosis, epitheliolysis (28,29). While these and other mechanisms are likely to contribute to the overall chemopreventive efficacy, the data supporting the importance of suppression of proliferation in chemoprevention is unequivocal.…”
Section: Discussionmentioning
confidence: 99%
“…These have been complemented by reports that PEG has inhibited proliferation in a wide variety of CRC cells lines (12,13,29) although, the mechanisms had remained largely unexplored. Thus, our data demonstrated that there was a striking inhibition of G1➝S phase progression suggesting that this was a key factor in the suppression of proliferation by PEG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation